The Impact of Customer Online Word of Mouth on Building Trust and Loyalty at Latika Beauty Care - Endang Setyadi; Budi Suhardjo; Ujang Sumarwan (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: Latika Beauty Care has shown significant revenue growth by leveraging online interactions with customers through organic and amplified online word of mouth (O-WoM). Choosing the best online word of mouth can enhance customer satisfaction, builds their trust and loyalty for brings their recommendations to other people being the new customer.Purpose: The objectives of this study are to analyze the impact of O-WOM on customer satisfaction, trust, and loyalty, and to build a recommendation strategy to increase consumer word of mouth.Design/methodology/approach: The study used quantitative methods supported by qualitative approaches, data was collected from 210 respondents who had used Latika’s services. The study applies Structural Equation Modeling (SEM) to evaluate the influence of O-wom on key variables.Finding/Result: The results indicate that both soft and hard selling O-wom have significantly impacted customer trust, satisfaction, and loyalty. Another result found that satisfaction has significantly impact on trust & loyalty. Trust has an impact on recommendations, but loyalty did not have impact on recommendation.Conclusion: This study found that O-WOM soft selling & hard selling significantly drive the customer trust, satisfaction and loyalty, both trust & loyalty also give and impact in increasing purchasing recommendation by customer. The recommended strategy to increase consumer intention to recommend Latika Beauty Care Clinic services is strengthening trust, optimizing e-WOM, increasing consumer loyalty, developing pricing, product and promotion strategies.Originality/value (State of the art): This study contributes to academic literature by identifying factors in building trust and loyalty of Latika Beauty Care Customers through online word of mouth soft selling and hard selling that never been analyzed before. And also, to give the management a recommendation in enhancing their marketing strategy as better than before. Keywords: customer satisfaction, digital marketing, consumer loyalty, online word of mouth, customer trust